1996
DOI: 10.1006/dbio.1996.0248
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Distal-less Gene Expression and Inductive Interactions in the Head of the Direct Developing FrogEleutherodactylus coqui

Abstract: The direct developing frog Eleutherodactylus coqui exhibits radical changes in its embryogenesis. A frog-like head forms directly with no appearance of a cement gland or several jaw cartilages characteristic of tadpoles, and limbs appear early in development. The numerous differences in the embryogenesis of E. coqui provide an opportunity to examine developmental causes for the evolutionary shift from biphasic to direct development. We have cloned DNA fragments corresponding to four E. coqui genes related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 0 publications
5
28
0
Order By: Relevance
“…(41,42) Since the head skeleton is derived largely from the cranial neural crest, the migration pattern of this embryonic cell type was studied to determine whether the alterations in cranial morphology could be due to modifications in the positioning of neural crest streams. (33,43) However, the spatial patterning of the cranial neural crest streams does not appear to have been altered during the evolution of direct development, which is surprising given the dramatic alteration in cranial skeletal ontogeny.…”
Section: Elimination Of Tadpole-specific Structuresmentioning
confidence: 99%
See 4 more Smart Citations
“…(41,42) Since the head skeleton is derived largely from the cranial neural crest, the migration pattern of this embryonic cell type was studied to determine whether the alterations in cranial morphology could be due to modifications in the positioning of neural crest streams. (33,43) However, the spatial patterning of the cranial neural crest streams does not appear to have been altered during the evolution of direct development, which is surprising given the dramatic alteration in cranial skeletal ontogeny.…”
Section: Elimination Of Tadpole-specific Structuresmentioning
confidence: 99%
“…Heterospecific transplants of either presumptive cement gland or lateral line tissue between E. coqui and biphasic amphibians indicated that, while the E. coqui embryo still appears capable of sending out inductive signals for both cement gland and lateral line formation, its ectoderm has lost the ability to respond to these signals by differentiating into these larval structures. (33,34) Identification of the molecules implicated in the generation of tadpole-specific structures in Xenopus has allowed comparative studies to be performed in E. coqui. The distal-less (dll) genes are homeodomain proteins expressed in cranial neural crest cells and in the developing cement gland of Xenopus embryos.…”
Section: Elimination Of Tadpole-specific Structuresmentioning
confidence: 99%
See 3 more Smart Citations